Notary as the Frontline of Money Laundering Prevention - Rezki Amaliah Rusli; Masykur, Hamidi; Laila, Fathul (The Islamic Education and Multiculturalism Foundation, 2024)
This research examines the implementation of Government Regulation Number 43 of 2015, especially Article 3, related to the obligation of notaries as reporting parties in preventing money laundering crimes. The research method used to answer the existing problems is Sociolegal Legal research or commonly used as empirical juridical research. The results show that in practice, notaries still face a number of obstacles in carrying out the obligation to report suspicious financial transactions. The legal dilemma that arises in relation to this reporting obligation is often a challenge for notaries. This study further explores the factors that cause these obstacles and their implications for the effectiveness of preventing money laundering crimes.